Closing the Genotype-phenotype Gap - Yip, Y. L.; Section Editor for the IMIA Yearbook Section on Bioinformatics (Yearbook of Medical Informatics, 2010)
Objectives: To summarize current excellent research in the field of bioinformatics.Method: Synopsis of the articles selected for the IMIA Yearbook 2010.Results: The selection process for this yearbook’s section on Bioinformatics results in five excellent articles highlighting the progress made in advancing the understanding of genotypephenotype relationship, and their concrete application in clinical settings. First, next generation sequencing techniques have allowed the discovery of an ever larger number of genetic variations at a greater resolution, and methods were developed to ensure accurate data analysis. Second, innovative approaches were applied to gene expression data to allow its link to a wider phenotypic spectrum and to enhance its use for disease understanding. Third, there is a notable trend in visualizing diseases as network rather than individual entities, and this has provided new insights for disease interpretation. The progress mentioned above is further aided by continual development in bio-ontologies which provide means for semantic, and thus phenotype, comparison.Conclusions: The current literature showed a tightening link between genotype and phenotype, placing us one step closer to a better disease classification, patient stratification as well as the development of personalized medicine.
Keywords: Medical informatics; International Medical Informatics Association; yearbook; bioinformatics; genotype-phenotype relationships; bioontologies; semantic similarity